Pesquisa de Vibrio no cultivo do camarão marinho Litopenaeus vannamei no Estado do Ceará - Costa, Renata Albuquerque (2006)
Infections with bacteria of the genus Vibrio represent a major challenge to shrimp farmers today. Some species of vibrios, autochthonous of marine and estuarine environments, can cause severe infection in livestock, leading to economic loss and, when communicated to marketed foods, public health hazards. The objective of the present study was to identify and determine the incidence of vibrios present in a marine shrimp (Litopenaeus vannamei) culture in Northeastern Brazil. The study covered two culture cycles of L. vannamei, from May to November 2005, on a shrimp farm located in the estuary of Rio Coreaú (Ceará). Analyses were based on 24 samples of inflow water, 24 samples of pond water, and 24 samples of postlarval, juvenile and adult shrimp. The outcome measures included most probable number (MPN) of vibrios, number of sucrose-positive and negative strains, species identification and susceptibility to antibiotics. Vibrio concentrations were higher in pond water and shrimp samples than in inflow water samples. Out of 76 strains isolated from samples of shrimp at different development stages 14 species were identified, the most prevalent of which were V. harveyi and V. cholerae (in postlarvae), V. cholerae, V. anguillarum, V. alginolyticus and V. harveyi (in juveniles), and V. parahaemolyticus, V. harveyi and V. anguillarum (in adults). The hardiest species was V. cholerae of which one third out of 12 strains tested were resistant to sulfazotrim, one fourth to ampicillin, and one third to ceftriaxone. Depending on culture conditions, a high incidence of vibrios, as observed in the present study, may lead to substantial losses for the shrimp farming industry. In addition, the possibility of communicating pathogenic strains to marketed foods represents a major concern to public health.